Networking and Securing Botswana’s Public Health Care System (BPHS) to enable a secure digitalized patient-centered environment. (Journal of Health Informatics in Africa, 2019)
Background and Purpose: The aim of the research was to investigate and develop an e-health mobile application with associated algorithms for use in managing patient information collection. The research explored the current role of Information Technologies (ICTs) in the Botswana Public Healthcare System (BPHS). Specifically, it dealt with elucidating, discussing and understanding the current status of BPHS and ICTs role in BPHS in relation to the utilisation of Electronic Health Records (EHRs). The author explored the current BPHS ways of gathering and processing patient information, categorization of the current BPHS and users’ satisfaction levels with it and ascertained people’s behaviours towards employment and utilisation of ICTs in health.Methods: Triangulation of quantitative and qualitative methods was followed, with questionnaires, interviews and observation techniques employed to draw conclusions.Results: There was strong evidence that many users showed dissatisfaction with BPHS, which is mostly paper oriented and manual, and indicated an embracement of mobile applications in health.Conclusions: The study concluded that the current BPHS is mostly paper based and the satisfaction levels of users negate such systems in this modern era of utilisation of ICTs. In conclusion, the author designed and developed a working prototype for BPHS.